2021
DOI: 10.3389/fmed.2021.660614
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal MicroRNA-181a Derived From Mesenchymal Stem Cells Improves Gut Microbiota Composition, Barrier Function, and Inflammatory Status in an Experimental Colitis Model

Abstract: Background: Mesenchymal stem cell (MSC)-derived exosomes (Exos) are recently proved to be a promising candidate for ulcerative colitis (UC), but the mechanism remains unclear. We investigated the effects of MSC-derived exosomal microRNA-181a (miR-181a) on gut microbiota, immune responses, and intestinal barrier function in UC.Methods: Human bone marrow MSC-derived Exos were extracted and identified via transmission electron microscopy (TEM), Nanoparticle Tracking Analysis (NTA), and Western blotting. Dextran s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…miRNAs are singlestranded non-coding RNA molecules of approximately 22 nucleotides in length that play important roles in regulating gene expression and biological function (79). In recent years, studies have shown that EV-derived miRNA expression is related to gut microbiota and intestinal barrier function (80)(81)(82). Mice deficient in IECs miRNA showed intestinal dysbiosis and exacerbation of colitis, which ameliorated after transplantation with fecal EV-derived miRNA from wild-type mice (80).…”
Section: Extracellular Vesicle and Mirnamentioning
confidence: 99%
See 3 more Smart Citations
“…miRNAs are singlestranded non-coding RNA molecules of approximately 22 nucleotides in length that play important roles in regulating gene expression and biological function (79). In recent years, studies have shown that EV-derived miRNA expression is related to gut microbiota and intestinal barrier function (80)(81)(82). Mice deficient in IECs miRNA showed intestinal dysbiosis and exacerbation of colitis, which ameliorated after transplantation with fecal EV-derived miRNA from wild-type mice (80).…”
Section: Extracellular Vesicle and Mirnamentioning
confidence: 99%
“…Another study found that EV-derived miRNAs of dietary ginger can induce IL-22 production to improve intestinal barrier function and thus ameliorate intestinal inflammation ( 83 ). A recent study showed that exosome miR-181a derived from MSCs alleviated colitis by improving gut microbiota imbalance and intestinal barrier function and reducing pro-inflammatory factor secretion ( 82 ). Taken together, the above results suggest that some EV-derived miRNAs in the intestinal tract may inhibit the progression of SLE by improving gut microbiota homeostasis and intestinal barrier function.…”
Section: Mechanisms Of Gut Microbiota Dysbiosis In Slementioning
confidence: 99%
See 2 more Smart Citations
“…For example, overexpression of miR-125b targeting SIRT7 in bone marrow MSC-derived exosomes down-regulated the levels of Bax, caspase-3 apoptotic proteins and IL-1β, IL-6, TNF-α inflammatory factors, and up-regulated the expression of Bcl-2, in order to repair the myocardial injury of I/R-rats ( 73 ). In addition, miR-181a delivered by exosomes of MSCs may inhibit the inflammatory response through c-Fos and promote the polarization of Treg cells to protect myocardial injury caused by miRs ( 74 77 ). These results suggest that donor cell engineering allows for directed cargo loading of small nucleotides into EVs, providing an effective therapeutic strategy for ischemia-reperfusion injury.…”
Section: Engineering Strategies Of Evs In the Diagnosis And Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%